Pelatihan Penyusunan Soal HOTS untuk Guru di SMK Kota Medan: The Training of HOTS Questions for Teachers at Medan City Vocational School - Harun Sitompul; Zulkifli Matondang; Eka Daryanto; Sapitri Januariyansah; Haryani Pratiwi Sitompul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
HOTS is a fundamental skill that prospective workers must possess. Vocational High Schools, as workforce printers, must pay attention to the HOTS of prospective graduates so that they can be absorbed in the world of work. However, Vocational High Schools experience many obstacles in forming prospective HOTS graduates. One of them is the teacher's ability to prepare HOTS questions. Based on the results of initial observations, similar obstacles were also faced by SMKN 14 Medan and SMKS Al-Fattah. The purpose of this activity is to provide training on the preparation of HOTS questions to teachers in SMK. The activity method used presentation, discussion, demonstration, and assignment techniques. Activities were grouped into three stages, namely preparation, implementation, and evaluation—the results of activities run effectively by the plan. The participants participated in the activity enthusiastically. The results of the FGD showed an increase in the ability of teachers to prepare HOTS questions. The skills of preparing HOTS vocational teachers still need to be considered because HOTS is one of the key skills of prospective workers.